Research Progress on Continuous-Flow Nitrification Technology and Equipment - Zhipeng Zheng; Xiaobing Liang; Xiaorong Zhou; Rui Zhu; Fengfan Liu (Pharmaceutical Fronts)
The mixture of concentrated nitric and sulfonic acids (mix acid) has been commonly used as a nitration reagent for the preparation of nitro compounds. Compared with the traditional batch reactor, continuous-flow nitrification technology has been recognized by the industry for its higher safety and production efficiency. As a frontier and hot topic in chemical engineering, continuous-flow reactor has gradually become an important platform for the development of new equipment, new processes, and new products for drug synthesis. Combining flow chemistry with real-time process analysis allows the study of reaction kinetics and the monitoring of the chemical synthesis process. In this work, the application of continuous-flow reaction technique in nitrification of aromatic rings, aromatic heterocycles, and aliphatic compounds is summarized. Based on process analysis technology and multistep series continuous-flow reaction to synthesize nitro compounds, the safe technology of nitrification reaction is realized in the green safety process.